Multi-Stakeholder Opinion Statement on the Care of Individuals Born with Differences of Sex Development: Common Ground and Opportunities for Improvement - GÜRAN, TÜLAY (My University, 2024)
Background: In the last 15 years, the care provided for individuals born with differences of sex development (DSD) has evolved, with a strong emphasis on interdisciplinary approaches. However, these developments have not convinced some stakeholders to embrace the current model of care. This care model has also paid insufficient attention to socio-cultural differences and global inequalities. Summary: This article is an opinion statement, resulting from in-depth discussions and reflection among clinicians, patients, and family support organizations based in the USA and Europe, where we seek areas of common ground and try to identify opportunities to further develop resources. The product of these conversations is summarized in 10 panels. The corresponding sections provide additional discussion on some of the panel items. Key Messages: Participants identified areas of agreement, gained a deeper understanding of the reasons behind disagreements on certain matters, and identified the necessary steps to foster future consensus. We offer preliminary recommendations for guiding clinical management and resource allocation. By promoting a broader consensus, we aim to enhance the quality of care and well-being for individuals of all ages who have a DSD.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ENDOKRİNOLOJİ VE METABOLİZMA; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; ENDOCRINOLOGY & METABOLISM; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Yaşam Bilimleri; Pediatrics, Perinatology and Child Health; Endocrinology, Diabetes and Metabolism; Endocrinology; Life Sciences; Differences of sex development; Disorders of sex development; Interdisciplinary team; Intersex; Peer support; Psychosocial care Activism